Pengenalan Pembelajaran Model Product Based Learning pada TK Islam Terpadu Ar-Rajwaa - Roby Roby; Zainal Abidin; F. Silvi Dwi Mentari; Yuanita Yuanita; Nur Hidayat; Daryono Daryono; Faradilla Faradilla; La Mudi; Riama Rita Manullang; Rusmini Rusmini; Haryatie Sarie (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This training aims to introduce and apply a product-based learning (PBL) approach in a kindergarten (TK) environment. PBL is a student-centered learning method where children learn through exploration, problem solving and collaboratively in producing a product. In the kindergarten context, PBL focuses on developing children's cognitive, social and motor skills through hands-on learning and writing activities. This training was developed for kindergarten teachers with a theoretical understanding of PBL, PBL planning methods that are adapted to child development, as well as creative and effective classroom implementation strategies. Educators are trained to design programs that connect to the kindergarten curriculum, conduct product-based learning, assess children's progress in critical thinking, communication and collaboration skills. The hope is that this training can help teachers create an interesting and meaningful learning environment for children, encouraging creativity, curiosity and enthusiasm for learning. It is hoped that the results of this training can improve the quality of children's education through the effective implementation of PBL.